Language Mixings in Heritage Language Education: A Systematic Review - Jiang, Yizhe (International Journal of Language and Literary Studies, 2021)
The overarching research question for this paper is what work has been done on heritage languages worldwide through a language mixing lens. Given the increasing research interest in this topic and the scarcity of previous secondary studies, a systematic review was conducted on the empirical data at the intersection of language mixing and heritage language education, in and out of schools. Thematic analysis and frequency analysis were carried out on qualified empirical sources gathered from Scopus, Web of Science, and Linguistics and Language Behavior Abstracts (LLBA). After sharing backgrounds on heritage language education and language mixing with relative terms and perspectives, the paper presents findings from the review based on 23 peer-reviewed empirical journal articles, focusing specifically on three aspects: (a) the main theoretical approaches and definitions employed for language mixing; (b) the characterization of language mixing for instruction and its impacts on heritage language education; (c) the parent and community language mixing activities for children’s heritage language learning. The limitations of the existing studies and the implications for educators and researchers are later discussed. It is hoped that this article will further our knowledge on this topic and provide pointed implications for future education and research.